2018
DOI: 10.1080/0284186x.2018.1445285
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting local control of pulmonary oligometastases treated with stereotactic body radiotherapy

Abstract: SBRT achieved an excellent LC of 85% at 2 years. Although retrospective in nature, our study identified three factors associated with inferior LC. These factors may help to refine SBRT practice for pulmonary oligometastases in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 33 publications
5
57
0
Order By: Relevance
“…The median number of fractions employed was 3 (range: 1-8), how many lesions were treated with SFRS remains unclear. Other trials rarely report significance of BED and fractionation regiments on treatment outcome for metastases according to size (9,21). Nevertheless, the existing data on size-adapted SFRS for lung metastases as well as primary lung tumors is promising with 1 year LC rates varying from 89.1%-93.4 % (15,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of fractions employed was 3 (range: 1-8), how many lesions were treated with SFRS remains unclear. Other trials rarely report significance of BED and fractionation regiments on treatment outcome for metastases according to size (9,21). Nevertheless, the existing data on size-adapted SFRS for lung metastases as well as primary lung tumors is promising with 1 year LC rates varying from 89.1%-93.4 % (15,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are comparable with the current findings in the literature (Tab. 7) (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…SBRT is a modern radiation technique that delivers a high dose to the tumor in a small number of fractions. For patients with pulmonary oligometastatic disease, SBRT achieves excellent local control and is associated with limited toxicity [9][10][11][12][13][14][15][16][17][18][19][20][21]. Patients treated with SBRT are usually not suitable for surgery, are often elderly and have multiple co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In a large series of oligometastatic patients from different primaries and various sites, the administration of systemic therapies prior to SBRT predicted a higher risk of progression, with an HR of 1.19 [35]. Similarly, Sharma et al reported poorer local control in patients previously treated with chemotherapy in a large database of 327 pulmonary oligometastases from miscellaneous primary tumors [36].…”
Section: Discussionmentioning
confidence: 95%